2021
DOI: 10.3390/nu13041378
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and Vitamin D Deficiency in Patients with Crohn’s Disease: Pathological Conditions That Should Be Linked Together

Abstract: Sarcopenia is a prevalent condition in patients with Crohn’s disease (CD), representing an independent predictor factor for the development of major postoperative complications. Thus, a proper assessment of the muscle strength, by using different validated tools, should be deemed an important step of the clinical management of these patients. Patients with CD are frequently malnourished, presenting a high prevalence of different macro- and micro-nutrient deficiencies, including that of vitamin D. The available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Crohn’s disease (CD) is an inflammatory bowel disease that can involve any part of the gastrointestinal tract and is characterized by alternating relapses and remissions, which can result in a variety of complications, such as intestinal strictures, perforations, and fistulas, severely reducing the quality of life of patients ( 1 ). During the course of chronic inflammatory disease in CD patients, 65–75% of patients may experience malnutrition due to dietary restrictions and impaired digestion and absorption ( 2 ), while the chronic malnutrition status may lead to an imbalance of the intestinal flora and further exacerbate the inflammatory response of the intestine ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Crohn’s disease (CD) is an inflammatory bowel disease that can involve any part of the gastrointestinal tract and is characterized by alternating relapses and remissions, which can result in a variety of complications, such as intestinal strictures, perforations, and fistulas, severely reducing the quality of life of patients ( 1 ). During the course of chronic inflammatory disease in CD patients, 65–75% of patients may experience malnutrition due to dietary restrictions and impaired digestion and absorption ( 2 ), while the chronic malnutrition status may lead to an imbalance of the intestinal flora and further exacerbate the inflammatory response of the intestine ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D plays the important role in regulating body metabolism and maintaining normal physiological functions in the human body, vitamin D deficiency or vitamin D insufficiency could cause a series of diseases including osteomalacia [10], rheumatoid arthritis [11], diabetes mellitus [12], Crohn's disease [13] and immune diseases [14]; seasonal emotional disorders are also associated with vitamin D deficiency [15], different age stages including pregnancy and early childhood growth also require vitamin D supplementation [16,17]. The evidences demonstrated that people with limited outdoor activities, vegetarians, patients with celiac disease, people taking some kinds of special medications, and other risk factors including high latitude, lack of sunlight, age, obesity also could result in the vitamin D deficiency those results demonstrated that the vitamin D deficiency may affect the situation of the adult diabetes mellitus patients, and gender, age, and seasons could be the main risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia due to malnutrition has emerged as an important problem for CD patients. 16 17 18 There have been efforts made to quantify the body composition of CD patients using the psoas muscle area on routine MRI. 19 In our study, psoas muscle thickness was significantly lower in CD patients on initial abdominal CT (19.2 mm vs. 22 mm, p =0.040).…”
Section: Discussionmentioning
confidence: 99%